Addition of Tannin in Lamb Diets after Weaning: Impact on Performance and Hematological and Biochemical Variables - Lucianer, Eduardo; Schafer da Silva, Aleksandro; Cazarotto, Chrystian Jassana; Alba, Davi Fernando; Griss, Luiz Gustavo; Zampar, Aline; Vedovatto, Marcelo; Kessler, Julcemar Dias (Acta Scientiae Veterinariae, 2019)
Background: In ruminants, the weaning period is a critical phase, because these young animals are allocated to various facilities and receive different feeds. Alternatively, supplements and additives can be used. The tannins are polyphenols produced by plants; constitute a group of complex secondary metabolic factors that inhibit the consumption by herbivores or the development of microbial agents. The objective of this study was to determine whether the addition of condensed tannin extract from quebracho trees (Schinopsis lorentzii) in lamb diets after weaning would have beneficial effects on growth and health. Materials, Methods & Results: Forty lambs were assigned randomly to 1 of 4 treatments (10 lambs/treatment): T1 (0%; control), T2, T3, and T4 was 0.3, 0.6 and 0.9 % of quebracho extract in the diet, respectively. The T2 (0.3%) lambs had greater body condition scores (P = 0.005), and although they did not differ significantly, they had numerically greater body weight (P = 0.067) and weight gain (P = 0.072), than the control lambs. The anthelmintic and anticoccidial effect was not possible to verify because no animals in any group were naturally infected by helminths or coccidia. The T4 lambs had greater numbers of erythrocytes (days 10 and 40) [P < 0.05], greater hemoglobin concentrations (days 10 and 40), and greater numbers of total leukocytes (day 10) as a result of greater numbers of neutrophil at the end of the adaptation period (day 10) compared to T1. The T3 and T4 lambs had greater (P < 0.05) serum total protein (days 10 and 40) because of greater concentration of serum globulins (days 10 and 40) compared to T1, suggesting that the addition of tannin stimulated the immune system. The addition of quebracho in the diet affected serum concentrations of glucose, triglycerides, and cholesterol at some times and treatments (P < 0.05). However, these changes did not follow a pattern; this finding only suggested that there was an influence on the metabolism of carbohydrates and lipids. The T2 lambs showed no differences on hemogram or serum clinic biochemistries (P > 0.05); however, they had a greater body condition scores than T1 (P < 0.05). Discussion: According to literature, if condensed tannins are supplied in moderate quantities (≤ 5% of diet) to ruminants, they can prevent bloating, increase the supply of undegraded protein in the rumen and improve the use of essential amino acids. It is also known that tannins in diet may increase urea recycling efficiency by increasing the concentration of urea in saliva and salivary flow into the rumen. Studies observed that cattle and sheep given feed containing condensed tannins had higher production of wool, meat, milk, and ovulation rates in females, desirable effects on animal production. According to the literature, dietary supplementation with tannins from chestnut and quebracho (2 g/kg of feed) to Holstein cattle changed the composition of the ruminal microbiota, particularly the bacteria that degrade fiber and starch, reducing the abundance of Prevotella and Fibrobacter, favoring Ruminococcaceae and other members of the phylum Firmicutes, increasing the pH and decreasing urease activity in ruminal fluid. Therefore, when tannins are supplemented at low concentrations, they can stimulate the intake and utilization of essential amino acids in the small intestine, increasing performance and exerting an anthelmintic effect. Our study found that the addition of 0.3% of quebracho in the diet improved lamb growth and health after weaning. It is therefore an additive that can be used to feed lambs in critical post weaning period.